PENGARUH KOMPOS ASAL KULIT JENGKOL (Phitecolobium jiringa (Jack) Prain ex King) TERHADAP CIRI KIMIA TANAH SAWAH DAN PRODUKSI TANAMAN PADI - Gusnidar Gusnidar; Yulnafatmawita Yulnafatmawita; Rosa Nofianti (Jurnal Solum, 2011)
This research had been conducted in the greenhouse and the Soil Laboratory of the Faculty of Agriculture, Andalas University, Padang, West Sumatera. The study was done from March until October 2011.  The aims of this research were to get the effect of compost from jengkol shell on chemical properties of paddy soil and rice yield.  The experiments were conducted in a greenhouse and the experimental units were arranged based on completely randomized design (CRD).  The treatments were application of compost K0 = 0 tons/ha (0 g/pot), K1 = 5 tons/ha (20 g/pot), K2 = 10 tons/ha (40 g/pot), K3 = 20 tons/ha (80 g/pot), K4 = 40 tons/ha (160 g/pot).  The data were compared to the criteria of soil chemical properties and plant data were statistically analysed for the variance.  If the F calculated > F table, the analyses were continued   by using DNMRT at 0.05 level of significance.  The results showed that application of 160 g compost/pot increased soil pH by 21.78%, N-total by 123.07%, organic-C by 65.84%, available P by 93.55%, K exch. by 238.35%, Ca exch. by 133.33%, Mg exch. by 90.00%, CEC by 238.90%, Cu exch. by 54,10%, as well as the yield by 12,68% compared to the treatment without compost application.Keywords : jengkol, nutrients, paddy soil, production